Perancangan Aplikasi Grup Touring Berbasis Mobile Menggunakan Metode Md5 - Salammudin; Marwan, Andi; Handoko, Divi (Ali Institute of Research and Publication, 2022)
The development of technology today is so fast. Technology makes changes in human civilization. In the current era of globalization, technological developments are increasingly rapid, especially internet technology, even now telecommunication tools, especially mobile-based ones, really need internet access to be easily connected. A group/Community is a network of several individuals in the form of kinship, then bind each other in increasing the socialization of fellow networks, mutually support and support each other, provide information, have a sense of belonging to a close unity, and become the social identity of motorized vehicle users. Based on these problems we need a system that can solve these problems, this is what drives the authors to design software to make it easier for leaders, members, and the community to create a better community by raising.